EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAM GAMES TOURNAMENT BERBANTUAN MEDIA WORDWALL DALAM PEMBELAJARAN BAHASA INDONESIA MATERI SEHATLAH RAGAKU TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SD GMIT PALIBOO - Foni Demince Mau; Yermia S. Wabang; Petrus Mau Tellu Dony (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Foni Demince Mau. 2586026038. The effectiveness of the cooperative learning model of the team games tournament type assisted by wordwall media in learning Indonesian language material sehatlah ragaku on the learning outcomes of fourth grade students of GMIT Paliboo Elementary School. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Tribuana Kalabahi University. Supervisor I Yermia Semuel Wabang, S.Pd., M.Pd. and Supervisor II: Petrus Mau Tellu Dony, S.Pd., M.Pd. This research is motivated by the low learning outcomes of fourth grade students in Indonesian language caused by the less than optimal use of varied learning models. This study aims to determine the effectiveness of the cooperative learning model of the team games tournament type assisted by wordwall media on the learning outcomes of elementary school students in Indonesian language. This study uses a quantitative method with a pre-experimental design of the one group pretest-posttest type. The research subjects were 33 students who were determined through saturated sampling techniques. The data collection technique was carried out through learning outcome tests in the form of pretest and posttest, with a pretest score of 60.45 and a posttest score of 82.06. The research instrument has undergone a material validity test of 97 and media 100 and reliability of 0.71118, as well as an analysis of the discriminatory power of all 30 questions were accepted and the level of difficulty of the 30 questions was concluded that they were neither too easy nor too difficult and met the criteria. Data were analyzed through a normality test of 0.214 and a hypothesis test using a paired sample t-test with the help of SPSS 22. The results of the study showed a significant increase in student learning outcomes after the implementation of the learning model. This is evidenced by the calculated t value of 9.136 which is greater than the t table of 1.694, so H0 is rejected and H1 is accepted. Thus, the cooperative learning model of the team games tournament type assisted by wordwall media in learning Indonesian language material sehatlah ragaku on the learning outcomes of fourth-grade students at SD GMIT Paliboo has proven effective in improving Indonesian language learning outcomes.